TAGUCHI METHOD APPLIED FOR THE INVESTIGATION OF CORROSION LEVEL ON METAL INERT GAS WELDING OF MILD STEEL - Fatchurrohman, Nanang; Chin, Low Tze; Na’am, Jufriadif (PATTIMURA UNIVERSITY, 2022)
Mild steel has a wide range of uses such as in the construction field, automotive field, machinery industry, cookware, and pipeline. Metal Inert Gas (MIG) welding act as an assembly method of mild steel. Corrosion level is a common problem that occurs in MIG welding on mild steel. In this study, the suitable welding parameters such as voltage, number of passes, and method of welding were chosen in the experimental testing and the experimental testing was planned by using the Design of Experiment (DoE) as part of Taguchi method. The welded mild steel specimens were evaluated using a corrosion test. The data analysis was done by using Taguchi method. For the parameter to be the optimum welding parameter, the corrosion level was as low as possible. In this case, the S/N ratio smaller is better common interest is chosen. By using the Minitab 18 software, the S/N ratio was calculated. Hence from the result, the optimum parameter is 9V voltage, three passes and the welding method was circle push.